2020
DOI: 10.2147/ijn.s264528
|View full text |Cite
|
Sign up to set email alerts
|

<p>Bifunctional Therapeutic Application of Low-Frequency Ultrasound Associated with Zinc Phthalocyanine-Loaded Micelles</p>

Abstract: Purpose: Sonodynamic therapy (SDT) is a new therapeutic modality for the noninvasive cancer treatment based on the association of ultrasound and sonosensitizer drugs. Topical SDT requires the development of delivery systems to properly transport the sonosensitizer, such as zinc phthalocyanine (ZnPc), to the skin. In addition, the delivery system itself can participate in sonodynamic events and influence the therapeutic response. This study aimed to develop ZnPc-loaded micelle to evaluate its potential as a top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 77 publications
1
15
0
Order By: Relevance
“…Wu et al [24] found that Au@BTO NPs combining with ultrasound had an excellent antibacterial efficiency against both Gram-negative E. coli and Gram-positive S. aureus , they deduced that the sonodynamic ROS generation induced lipid peroxidation in cytomembrane, which enhanced the permeability of cell membrane and finally led to the intracellular protein leakage and irreversible damage to bacteria. Martins et al [101] got the same result in cancer cells, they studied the application of zinc phthalocyanine (ZnPc) as a sonosensitizer and discovered that the level of cellular lipid peroxidation increased three times after sonication.…”
Section: Cellular Oxidation ─ Antibacterial Mechanism Of Rosmentioning
confidence: 80%
“…Wu et al [24] found that Au@BTO NPs combining with ultrasound had an excellent antibacterial efficiency against both Gram-negative E. coli and Gram-positive S. aureus , they deduced that the sonodynamic ROS generation induced lipid peroxidation in cytomembrane, which enhanced the permeability of cell membrane and finally led to the intracellular protein leakage and irreversible damage to bacteria. Martins et al [101] got the same result in cancer cells, they studied the application of zinc phthalocyanine (ZnPc) as a sonosensitizer and discovered that the level of cellular lipid peroxidation increased three times after sonication.…”
Section: Cellular Oxidation ─ Antibacterial Mechanism Of Rosmentioning
confidence: 80%
“…For example, Martins et al investigated the sonodynamic activity of ZnPc encapsulated in nanometric polymeric micelles of 1.2-distearoyl- sn -glyreco-3-phosphoethanolamine- N -[amino(polyethylene glycol)-2000] (DSPE-PEG). 95 Owing to the amphiphilic property of DSPE-PEG, the prepared micelles could dissolve insoluble drugs, greatly enhancing their solubility in aqueous media. This work also shown that DSPE-PEG micelles might improve ultrasonic cavitation activity, increasing the permeability of ZnPc to the skin and encouraging the generation of ROS.…”
Section: The Sonosensitizers In Antibacterial Sdtmentioning
confidence: 99%
“…Due to poor water solubility and decreased penetration, ZnPc molecules are encapsulated in DSPE–PEG micelles and subjected to skin cancer treatment. Data showed that the low-frequency ultrasound irradiation of ZnPc-loaded micelles generates reactive oxygen species and stimulates lipoperoxidation in the skin that would eventually lead to tumor cell death [ 21 ]. Similarly, Liu et al [ 22 ] reported that the encapsulation of meta -tetra(hydroxyphenyl)chlorine, a photosensitizer, in P23 micelles effectively increased blood circulation kinetics and ultimately enhanced selective photocytotoxicity on A431 cells.…”
Section: Types Of Nanoparticlesmentioning
confidence: 99%